The Implementation Of Active Learning Strategies In ESL Classroom: Students' Perspectives - Rosnani, Ismail; Siti Norzaimalina, Abd Majid (UTM, 2023)
Student participation plays a critical role in fostering an efficient learning process within an ESL classroom. One innovative approach to promote learning engagement is the integration of active learning strategies into classroom activities. Even though an active learning approach can potentially improve students’ engagement and learning outcomes, there is a lack of understanding of students’ perspectives on the efficacy of these strategies and the overall language learning experience. Therefore, the main objective of this study is to explore students’ perspectives regarding the efficacy of employing an active learning approach in ESL classroom learning activities. To facilitate this investigation, the active learning approach was implemented over eight weeks among diploma-level students with diverse English proficiency levels. The primary data source was an open-ended survey administered using Google Forms. The responses received from 68 participants were mostly positive feedback, and the results were analysed using thematic analysis. The findings substantiate that many students preferred incorporating active learning activities, which benefits them in many ways throughout their learning experience. Subsequently, the implications of this study have spread into the broader field of instructional methods, leading educators to think about a paradigm change to more interactive and dynamic teaching strategies. Teachers can enhance their professional growth by seeking training and support to integrate active learning strategies into their ESL classrooms. Thus, future studies must examine the potential improvements that can further enhance the impact of active learning in ESL classrooms.